On-demand bioadhesive hydrogelbased on diazirine - Gao, Feng (2017)
On-demand hydrogel bioadhesives based on carbene crosslinking were synthesized and characterizedregards to a soft tissue bioadhesive. Several carbene precursors were conjugated onto sodium alginate and Poly (amidoamine) dendrimers (PAMAM). Results presented in this thesis demonstrated that hydrogel tissue adhesives based on carbene were effective in crosslinking synthetic and natural substrates. PAMAM-g-diazirine was fully crosslinked with the UV dosage of 6 J/cm2, and the UV wavelength required during this process was 365 nm, which falls into UVA range, suitable for clinical applications. The mechanical properties of this adhesive after crosslinking were tunable and highly predictable. Storage moduli of cured adhesive ranged up to 225 kPa. Generated carbene radicals acted as unselective crosslinkers, and they could insert into C-H bonds available on synthetic and natural substrates. The formed covalent bonds with adherent tissue (ex vivo swine aorta) resulted in maximum lap shear adhesion strength up to40 kPa. This value was 7 times higher than that of commercial fibrin glue approved for clinical practice. Exvivo cell culture experiments showed that the participation of diazirine and the UV irradiation did not lead to additional cytotoxic effect, although terminal NH2of backbone PAMAMstructure were anticipated to significantly reduce cell proliferation. Apart from UV activation of diazirine-grafted PAMAM, this macromolecule was found to crosslink at the -2 V vs. Ag/AgCl reference electrode. Thus, PAMAM-g-diazirine was able to crosslink and act as an adhesive activated by voltage in aqueous environment. Maximum lap shear adhesion strength accomplished by this adhesive was 80 kPa. Similar to the UV activated adhesive, the generated carbene allowed tunable mechanical properties. The proposed mechanism for electrocuring with diazirine is based on its reduction to diaziridine at the cathode, with subsequent oxidation to carbene. This low voltage activated aqueous adhesive was reported for the first time.